1991
DOI: 10.1002/jnr.490280212
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IGF‐I and insulin receptor genes in the rat central nervous system: A developmental, regional, and cellular analysis

Abstract: Using a solution-hybridization assay and specific oligonucleotidic probes, we have studied IGF-I and insulin receptor mRNAs in the rat central nervous system during development. The expression of mRNAs was maximal at embryonic day 15 and 20 for IGF-I receptors, and at embryonic day 20 and the day of birth for insulin receptors. After birth, the expression of both receptor transcripts decreased and reached minimal levels in the adult. At the time at which these transcripts were maximally expressed (embryonic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(44 citation statements)
references
References 56 publications
4
39
0
Order By: Relevance
“…Previous studies using in situ hybridization and radiolabeled insulin suggest that insulin receptor mRNA and protein are widely expressed in brain (Havrankova et al, 1978;Baron Van Evercooren et al, 1991;Kar et al, 1997). However, insulin can bind to other cell surface proteins, including the insulin-like growth factor 1 receptor (IGF1R; Sosa et al, 2006), and therefore insulin binding may overestimate the extent of insulin receptor expression.…”
Section: Synapse Number Is Selectively Increased In Insulin Receptorementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using in situ hybridization and radiolabeled insulin suggest that insulin receptor mRNA and protein are widely expressed in brain (Havrankova et al, 1978;Baron Van Evercooren et al, 1991;Kar et al, 1997). However, insulin can bind to other cell surface proteins, including the insulin-like growth factor 1 receptor (IGF1R; Sosa et al, 2006), and therefore insulin binding may overestimate the extent of insulin receptor expression.…”
Section: Synapse Number Is Selectively Increased In Insulin Receptorementioning
confidence: 99%
“…However, insulin can bind to other cell surface proteins, including the insulin-like growth factor 1 receptor (IGF1R; Sosa et al, 2006), and therefore insulin binding may overestimate the extent of insulin receptor expression. To characterize insulin receptor protein expression in the brain, immunostaining was performed on permeabilized mouse brain sections using an antibody that is specific for insulin receptors and does not cross-react with IGF1Rs (EntinghPearsall and Kahn, 2004;Baudler et al, 2005). This antibody (clone C19) recognizes an intracellular epitope of the ␤-subunit of the insulin receptor.…”
Section: Synapse Number Is Selectively Increased In Insulin Receptorementioning
confidence: 99%
“…IGF-I gene expression is abundant in the developing nervous system (13)(14)(15)(16)(17)(18). IGF-I mRNA is selectively concentrated in the large principal neurons of functionally related sensory and cerebellar relay systems during a late predominantly postnatal phase of neural development (18).…”
mentioning
confidence: 99%
“…Also, several studies have shown that IGFs have potent and highly specific effects on oligodendrocytes in vitro (7)(8)(9)(10). However, except for the olfactory system, very little IGF-I is normally detected in the mature rodent brain (16)(17)(18).…”
mentioning
confidence: 99%
“…Moreover, astroglial cells appear to express an IGF1R similar to that found in peripheral cells (Baron-Van Evercooren et al 1991). Interestingly, these receptors differ from the IGF1Rs found in neurons, which have distinct glycosylated residues, as evidenced by in vitro studies (Burgess et al 1987).…”
Section: Discussionmentioning
confidence: 90%